Fc-optimized antibodies elicit CD8 immunity to viral respiratory infection - Bournazos, Stylianos; Corti, Davide; Virgin, Herbert W.; Ravetch, Jeffrey V. (Nature (London), 2020)
Antibodies against viral pathogens represent promising therapeutic agents for the control of infection, and their antiviral efficacy has been shown to require the coordinated function of both the Fab and Fc domains 1 . The Fc domain engages a wide spectrum of receptors on discrete cells of the immune system to trigger the clearance of viruses and subsequent killing of infected cells 1 – 4 . Here we report that Fc engineering of anti-influenza IgG monoclonal antibodies for selective binding to the activating Fcγ receptor FcγRIIa results in enhanced ability to prevent or treat lethal viral respiratory infection in mice, with increased maturation of dendritic cells and the induction of protective CD8 + T cell responses. These findings highlight the capacity for IgG antibodies to induce protective adaptive immunity to viral infection when they selectively activate a dendritic cell and T cell pathway, with important implications for the development of therapeutic antibodies with improved antiviral efficacy against viral respiratory pathogens. An antibody Fc domain variant with enhanced binding to an activating Fc receptor on dendritic cells promotes the induction of a protective CD8 T cell response.